[Rezension von: Jarzebowsky, Claudia, Kindheit und Emotion: Kinder und ihre Lebenswelten in der europäischen Frühen Neuzeit] - Büttner, Andreas (The English historical review, 2020)
Claudia Jarzebowski’s book on childhood and emotion combines two thriving fields of scholarly interest with a focus on the early modern period. One would expect her to travel on rather well trodden research paths. However, as the author points out in her introduction, this is hardly the case, although several recent studies have already addressed the issue. Jarzebowski’s aim is to emphasise the perspective of children, with the ultimate goal of rewriting the history of childhood itself. Her underlying methodology is the deconstruction of biological categories, thus de-emphasising the role of biological parents (the father in particular) in favour of other significant adults. Defining childhood as a ‘social relation’ (pp. 4, 36) she furthermore decides to focus not only on young children but to include young adults of sixteen or even nineteen years of age.
Gesehen am 02.06.2021
Keywords: Rezension